STRUCTURAL-MORPHOLOGICAL CHANGES OF BONE TISSUE IN PATIENTS WITH CHRONIC RECURRENT HEMATOGENOUS OSTEOMYELITIS - Mukhitdinovich, Shamsiev Azamat; Sabirovich, Zainiev Sukhrob; Mamadjanovich, Makhmudov Zafar (International Journal of Psychosocial Rehabilitation, 2020)
To study the morphological features of the structure of bone tissue in patients with chronic recurrent hematogenous osteomyelitis.The studied material of scanning and transmission electron microscopy were bone fragments of 40 patients obtained during surgery from various pathologically altered sections of the affected tubular bones.Morphological studies revealed microscopic foci of necrosis, leukocyte infiltrates and microabscesses both in the main focus and in other parts of the bone marrow canal.Microabscesses detected by microscopy represent the morphological basis of chronic hematogenous osteomyelitis, can be located at a considerable distance from the main necrotic purulent focus and, under appropriate conditions, cause a relapse of the disease. Morphological studies have shown that surgical debridement of the lesion with ultrasonic cavitation of the lesion and the medullary canal contributes to a significant reduction in the degree of microbial contamination, followed by a decrease in pathological changes in bone tissue.